PENGEMBANGAN MEDIA FLASH CARD DALAM PEMBELAJARAN MEMBACA PERMULAAN KELAS I SD N 19 SITIUNG - Rusdi Indra Hasibuan; Riyadi Saputra; Julita Saputri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research is based on the problem that the initial reading ability of grade 1 students is still low, this can be seen from the results of the initial reading test which shows that only a few students achieved the minimum score for learning completeness. The aim of this research is to produce flash card learning media that valid, practical and effective. The type of research used is development research or Research and Development (R&D) using the ADDIE development model which consists of five stages, namely analysis, design, development, implementation (implementation), and the evaluation stage (evaluation). The results of the validity of the flash card media were validated by 2 validators, namely media expert validation which obtained a result of 83% which was categorized as very valid, and module expert validation which obtained a result of 62% which was categorized as valid. The results of the practicality of flash card media through the teacher response questionnaire by class I teachers were 82.5% categorized as very practical, while through the student response questionnaire the average results were 87% categorized as very practical. The effectiveness results were obtained from The learning test results of students at the main school obtained an average of 86% and were categorized as very effective.